Comprehension of the Posgraduated Teacher´s Practice and the Evaluation from their Perception - Javier Loredo Enríquez; Raúl Romero Lara; Patricia Inda Icaza (Universidad Autónoma de Baja California, 2008)
An approach to teachers' thinking processes is introduced as part of the first methodological stage of a research project whose main objective is to design an integral model of teaching practices in a specific institution. This was accomplished by interviewing the twenty best teachers as evaluated by students in 2007. Their general conceptions about teaching, students, education and particularly their stand with respect to teaching evaluation, reflected in experiences, recommendations and proposals were obtained. Their individual characteristics and their perspectives about classroom dynamics were also retrieved in data analysis. Guidelines to design the proposal of an innovative evaluation that allows for analysis, reflection and feedback intended at the improvement of their teaching is drawn from the interviews, as a partial result.